M-phase vanadium dioxide micro-flower composite graphene oxide material, preparation method thereof and application of M-phase vanadium dioxide micro-flower composite graphene oxide material in aqueous zinc ion battery
By combining the M-phase vanadium dioxide with graphene oxide with 3D microflower morphology, M-phase vanadium dioxide microflower composite graphene oxide material was prepared for the positive electrode of the aqueous zinc ion battery, which solved the problems of the existing materials' specific capacity decrease and poor safety during the magnification cycle, and achieved the effects of high capacity, good cycle stability and excellent magnification performance.
Patent Information
- Application Number
- CN202510099310.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
AI Technical Summary
The specific capacity of the existing water-based zinc ion battery cathode material drops rapidly during the ratio cycle, has poor rate performance, and the NH4VO3 in the raw materials is dangerous and has poor safety, which is not conducive to industrial production.
The M-phase vanadium dioxide composite graphene oxide material was prepared by composited with 3D microflower morphology, and used as the positive electrode active material for the positive electrode of the aqueous zinc ion battery.
At a current density of 0.5A/g, the reversible capacity of the aqueous zinc ion battery is as high as 502.35mAh/g, and at a current density of 5A/g, the reversible capacity is 329.36mAh/g, and after cycling for 1000 cycles at a current density of 5A/g, the reversible capacity retention rate is 88.32%, with excellent capacity, cycle stability and rate performance.
Smart Images

Figure CN119812282A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an M-phase vanadium dioxide micro-flower composite graphene oxide material and a preparation method thereof and application thereof in an aqueous zinc ion battery, belonging to the technical field of aqueous zinc ion batteries. Background Art
[0002] In the context of climate change and energy crisis, energy supply shortages and price surges are serious, and energy transformation is imperative. Although clean energy such as wind, solar and ocean energy has great potential, they have intermittent and regional disadvantages due to factors such as geography, climate and time. Therefore, more advanced energy storage equipment needs to be developed to promote the development of new energy.
[0003] Lithium-ion batteries were once a commonly used energy storage device due to their light weight, high energy density, and long cycle life. However, intrinsic factors such as the scarcity of lithium resources, the high cost of lithium battery preparation, and high safety risks have made them gradually lack competitiveness. At present, aqueous zinc-ion batteries (ZIBs) have become one of the most promising energy storage devices due to their extremely high safety, abundant surface Zn resources, eco-friendliness, high theoretical capacity (820 mAh / g), impressive long-term cycle stability, and superior rate capability.
[0004] Aqueous zinc-ion batteries are usually composed of a positive electrode, a zinc negative electrode, an electrolyte, a separator, etc. The positive electrode material is the key factor that determines the performance of aqueous zinc-ion batteries. At present, vanadium-based materials have broad application prospects in the positive electrode of aqueous zinc-ion batteries due to their high theoretical specific capacity, rich distribution, and low cost. Graphene materials have important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery due to their excellent optical, electrical, and mechanical properties. At present, there are reports on the composite preparation of vanadium-based materials and graphene materials for use as positive electrode materials in zinc-ion batteries.
[0005] Patent CN117913380A discloses a method for aqueous zinc ion battery NH4V4O 10 Preparation method of / rGO composite material, this patent uses oxalic acid to assist in the hydrothermal reaction of NH4V4O 10 Composited with rGO to prepare nanoflower-like NH4V4O 10 / rGO composite material, the prepared composite material can be used as a positive electrode material for zinc ion batteries. Although the aqueous zinc ion battery using the composite material as the positive electrode has a first-cycle discharge capacity of 595mAh / g at a current density of 0.1A / g, which has a high specific capacity, the specific capacity decreases rapidly in subsequent rate cycles, and the rate performance is poor. In addition, the NH4VO3 used in the raw materials is a hazardous chemical with strong oxidizing and corrosive properties, poor safety, and is not conducive to industrial production.
[0006] Patent CN109980205A discloses a vanadium pentoxide / graphene composite material and its preparation method and application. The patent adopts a hydrothermal method or a solvothermal method to compound vanadium pentoxide with graphene oxide (graphene) to obtain a vanadium pentoxide / graphene composite material. The prepared composite material can be used as a positive electrode material for zinc ion batteries. Although the cost is low, the specific capacity of the aqueous zinc ion battery using the composite material as the positive electrode is low (less than 300 mAh / g), which is difficult to meet the use requirements.
[0007] Among vanadium-based materials, vanadium dioxide can provide Zn 2+ The insertion / ejection of ions provides sufficient space to achieve a higher specific capacity. In addition, the researchers found that this structure can also alleviate the volume expansion effect caused by ion embedding and improve the cycle stability of the electrode material. More than 10 crystal phases of vanadium dioxide have been reported, including B phase, M phase, R phase, A phase and C phase. Among these different crystal phases of vanadium dioxide, M phase vanadium dioxide has been widely used because it can achieve reversible phase transition between primary metallic state and semiconductor state under room temperature conditions of crystallization. However, there are currently few reports on the use of M phase vanadium dioxide as positive electrode materials for aqueous zinc ion batteries. Patent CN110838583B discloses a carbon nanotube / M-phase vanadium dioxide composite structure and its preparation method and application in aqueous zinc ion batteries. The patent evenly distributes M-phase vanadium dioxide nanoparticles in the hollow tube cavity of carbon nanotubes and on the surface of the 3D network structure of the carbon nanotubes to form a carbon nanotube / M-phase vanadium dioxide composite structure, wherein the M-phase vanadium dioxide is in irregular granular form. However, the aqueous zinc ion battery using the composite structure as the positive electrode has a high conductivity at 2A·g -1 248mAh·g -1 The specific capacity is low.
[0008] In addition, the morphologies of M-phase vanadium dioxide reported so far are mostly spherical or rod-shaped, and there are few reports on M-phase vanadium dioxide with 3D microflower morphology. There are also few reports on the composite of M-phase vanadium dioxide with graphene materials for use as positive electrode materials for aqueous zinc-ion batteries, and there are even fewer reports on the composite of M-phase vanadium dioxide with 3D microflower morphology with graphene oxide materials for use as positive electrode materials for aqueous zinc-ion batteries. Summary of the invention
[0009] In view of the above problems existing in the prior art, the object of the present invention is to provide an M-phase vanadium dioxide micro-flower composite graphene oxide material and a preparation method thereof and application in aqueous zinc ion batteries.
[0010] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0011] An M-phase vanadium dioxide micro-flower composite graphene oxide material consists of graphene oxide (preferably single-layer graphene oxide) and M-phase vanadium dioxide with a 3D micro-flower morphology supported on the graphene oxide.
[0012] In one embodiment, the preparation of the 3D micro-flower morphology of M-phase vanadium dioxide comprises the following steps:
[0013] a) dissolving vanadium pentoxide and anhydrous oxalic acid in water, and then stirring and reacting at 55-75° C. for 5-10 hours to obtain a vanadium oxalate solution;
[0014] b) cooling the vanadium oxalate solution to room temperature, then adding hydrogen peroxide to the vanadium oxalate solution, stirring at room temperature for 25 to 50 minutes, then adding ethanol to the obtained reaction system, and then hydrothermally reacting at 170 to 200° C. for 20 to 24 hours. After the reaction is completed, collecting the solid product to obtain a powdery primary product;
[0015] c) The powdered primary product is placed in a muffle furnace, and under protective gas conditions, it is first calcined at 350-550° C. for 2-3 hours. After the calcination, it is cooled to room temperature with the furnace, and then calcined at 350-550° C. for 2-3 hours. After the calcination, it is air-cooled to room temperature to obtain M-phase vanadium dioxide with a 3D micro-flower morphology.
[0016] A preferred embodiment is that during the preparation process, the feed ratio of vanadium pentoxide, anhydrous oxalic acid, hydrogen peroxide and ethanol is (0.2-0.6) g: (0.6-1.2) g: (5-8) mL: (50-100) mL.
[0017] In a preferred embodiment, in step b), the operation of collecting the solid product is as follows:
[0018] After the reaction is completed, the precipitate is collected (specifically, the reaction solution can be filtered or centrifuged to obtain the precipitate), the precipitate is washed with a 15-30wt% ethanol aqueous solution and then dried at 55-65°C for 6-120 hours to obtain the powdery primary product.
[0019] In a preferred embodiment, in step c), the protective gas is an inert gas (eg, argon).
[0020] A preferred embodiment, in step c), the powdered primary product is placed in a muffle furnace, and under protective gas conditions, the temperature is first increased to 350-550°C at a heating rate of 5-10°C / min, and the temperature is initially kept warm and calcined for 2-3 hours at this temperature. After calcination, it is cooled to room temperature with the furnace, and then the temperature is increased to 350-550°C at a heating rate of 5-10°C / min, and the temperature is secondarily kept warm and calcined for 2-3 hours at this temperature. After calcination, it is air-cooled to room temperature to obtain M-phase vanadium dioxide with a 3D micro-flower morphology.
[0021] A method for preparing an M-phase vanadium dioxide micro-flower composite graphene oxide material comprises the following operations:
[0022] The M-phase vanadium dioxide with 3D micro-flower morphology and the ethanol dispersion of graphene oxide (preferably single-layer graphene oxide) are mixed at room temperature; the obtained mixed solution is first subjected to ultrasonic reaction for 1 to 1.5 hours, and then stirred at room temperature for 5 to 6 hours. After the reaction, the obtained mixed solution is dried at 55 to 65° C. for 6 to 12 hours to obtain the M-phase vanadium dioxide micro-flower composite graphene oxide material.
[0023] In one embodiment, the concentration of the ethanol dispersion of graphene oxide is 0.1-0.5 mg / mL, the amount of M-phase vanadium dioxide added is 5-15 mg, and the amount of the ethanol dispersion of graphene oxide added is 1-10 mL, that is, the mass ratio of M-phase vanadium dioxide:graphene oxide is (1-150):1, preferably (1-30):1, and further preferably (5-30):1.
[0024] In one implementation mode, during the ultrasonic reaction, the ultrasonic power is 50-60W.
[0025] The invention discloses an application of an M-phase vanadium dioxide microflower composite graphene oxide material in the positive electrode of an aqueous zinc ion battery, and is used as a positive electrode active material of the positive electrode of an aqueous zinc ion battery.
[0026] A method for preparing an aqueous zinc ion battery positive electrode comprises the following steps:
[0027] Taking M-phase vanadium dioxide microflower composite graphene oxide material as positive electrode active material, the positive electrode active material, conductive agent, binder and solvent are evenly mixed to form positive electrode slurry, and the obtained positive electrode slurry is coated on the surface of positive electrode collector and dried at 55-65° C. for 6-12 hours to obtain aqueous zinc ion battery positive electrode.
[0028] In one implementation scheme, the conductive agent is acetylene black, the binder is polyvinylidene fluoride (PVDF), the solvent is N-methylpyrrolidone (NMP), the mass ratio of positive electrode active material: conductive agent: binder is 7:2:1; and the positive electrode current collector is stainless steel.
[0029] An aqueous zinc ion battery comprises a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an aqueous electrolyte, wherein the positive electrode is the above-mentioned aqueous zinc ion battery positive electrode, the negative electrode is zinc foil, the separator is glass fiber, and the aqueous electrolyte is a 3M Zn(CH3F3SO3)2 aqueous solution.
[0030] Compared with the prior art, the present invention has the following significant beneficial effects:
[0031] The present invention composites M-phase vanadium dioxide with 3D microflower morphology with graphene oxide to obtain M-phase vanadium dioxide microflower composite graphene oxide material. The aqueous zinc ion battery using the M-phase vanadium dioxide microflower composite graphene oxide material as the positive electrode active material has a reversible capacity of up to 502.35 mAh / g at a current density of 0.5 A / g, a reversible capacity of 329.36 mAh / g at a current density of 5 A / g, and a reversible capacity retention rate of 88.32% after 1000 cycles at a current density of 5 A / g. The battery has excellent capacity, cycle stability and rate performance. Compared with the prior art, the present invention not only produces unexpected technical effects, but also has significant advancement. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 TEM image of the M-phase vanadium dioxide with 3D micro-flower morphology prepared in Example 1;
[0033] Figure 2 This is the XRD pattern of the M-phase vanadium dioxide micro-flower composite graphene oxide material prepared in Example 2;
[0034] Figure 3 The SEM images of the M-phase vanadium dioxide microflower composite graphene oxide material prepared in Example 2, a) is a SEM image with a scale of 1 μm, and b) is a SEM image with a scale of 200 nm;
[0035] Figure 4 This is a rate performance diagram of an aqueous zinc ion battery using the M-phase vanadium dioxide microflower composite graphene oxide material prepared in Example 2 as the positive electrode active material;
[0036] Figure 5 This is a rate performance diagram of an aqueous zinc ion battery using the M-phase vanadium dioxide with 3D micro-flower morphology prepared in Comparative Example 1 as the positive electrode active material;
[0037] Figure 6 This is the TEM image of the rod-shaped M-phase vanadium dioxide prepared in Comparative Example 2. DETAILED DESCRIPTION
[0038] The technical scheme of the present invention is further described in detail and completely below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0039] Example 1
[0040] 1. Preparation of M-phase vanadium dioxide with 3D micro-flower morphology
[0041] a) dissolving 2 g of V2O5 and 6 g of anhydrous oxalic acid in 30 mL of deionized water, and then stirring and reacting at 60° C. for 5 hours to obtain a vanadium oxalate solution;
[0042] b) cooling the obtained vanadium oxalate solution to room temperature, then adding 5 mL of hydrogen peroxide to the vanadium oxalate solution, stirring at room temperature for 30 minutes, the reaction solution is a wine red solution, and then transferring the obtained reaction system to the inner tank of a reactor, then adding 50 mL of ethanol (as a reducing agent) to the reaction system, and then hydrothermally reacting at 180° C. for 24 hours. After the reaction is completed, the reaction solution is centrifuged, and the separated precipitate is centrifuged and washed three times with 30% ethanol aqueous solution as a washing liquid, and then dried at 60° C. for 6 hours to obtain a powdery primary product;
[0043] c) The powdered primary product is transferred into a crucible, and then the crucible containing the product is placed in a muffle furnace. Under the protection of argon, the temperature is first increased to 350°C at a rate of 10°C / min, and the temperature is initially kept and calcined for 2 hours at this temperature. After the calcination, the furnace is cooled to room temperature, and then the temperature is increased to 350°C at a rate of 10°C / min, and the temperature is secondarily kept and calcined for 2 hours at this temperature. After the calcination, the temperature is air-cooled to room temperature to obtain M-phase vanadium dioxide with a 3D micro-flower morphology.
[0044] 2. Preparation of M-phase vanadium dioxide microflower composite graphene oxide materials
[0045] The prepared 3D micro-flower morphology of M-phase vanadium dioxide and 0.1 mg / mL of ethanol dispersion of single-layer graphene oxide were mixed at a ratio of 0.003 g / 5 mL (i.e., the mass ratio of M-phase vanadium dioxide: single-layer graphene oxide was 6:1); the resulting mixture was first subjected to ultrasonic reaction for 1 hour with an ultrasonic power of 55 W, and then magnetically stirred at room temperature for 6 hours. After the reaction, the resulting mixture was dried at 60°C for 6 hours to obtain a powdered M-phase vanadium dioxide micro-flower composite graphene oxide material.
[0046] 3. Preparation of VO2(M) microflower-GO positive electrode active material aqueous zinc ion battery
[0047] The prepared M-phase vanadium dioxide micro-flower composite graphene oxide material is used as the positive electrode active material of the positive electrode of an aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, and an appropriate amount of NMP is added. The mixture is stirred and mixed evenly to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of the aqueous zinc ion battery. The diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a diaphragm, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte. The existing button battery assembly technology is used to assemble a button-type aqueous zinc ion battery.
[0048] Figure 1 TEM image of the M-phase vanadium dioxide with 3D micro-flower morphology prepared in this example. Figure 1 It can be seen that the M-phase vanadium dioxide prepared in this embodiment has a 3D micro-flower morphology, wherein the diameter of a single 3D micro-flower structure is about 3 μm, and the petals are rod-shaped; the 3D micro-flower morphology provides a larger reaction area, which can accelerate the reaction of Zn 2+ When it is combined with layered graphene, it ensures the exposure of more active sites. When used in aqueous zinc-ion batteries, it is in situ electrochemically converted into a nanostructure with low crystallinity and minimal water solubility. Smaller particles and lower crystallinity are Zn 2+ Intercalation and fast charge transfer provide more reaction sites to cross the electrode / electrolyte interface with lower energy barriers, thus enabling aqueous Zn-ion batteries to achieve a capacity-stability trade-off.
[0049] The aqueous zinc ion battery prepared in this example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are shown in Table 1.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 is that: the M-phase vanadium dioxide with 3D micro-flower morphology is mixed with 0.1 mg / mL of ethanol dispersion of monolayer graphene oxide at a rate of 0.005 g / 5 mL (i.e., the mass ratio of M-phase vanadium dioxide: monolayer graphene oxide is 10:1), and the rest of the contents are the same as those described in embodiment 1. The specific preparation process is as follows:
[0052] 1. Preparation of M-phase vanadium dioxide with 3D micro-flower morphology
[0053] As described in Example 1.
[0054] 2. Preparation of M-phase vanadium dioxide microflower composite graphene oxide materials
[0055] The prepared 3D micro-flower morphology of M-phase vanadium dioxide was mixed with 0.1 mg / mL single-layer graphene oxide dispersion at a ratio of 0.005 g / 5 mL (i.e., the mass ratio of M-phase vanadium dioxide: single-layer graphene oxide was 10:1). The resulting mixture was first subjected to ultrasonic reaction for 1 hour with an ultrasonic power of 55 W, and then magnetically stirred at room temperature for 6 hours. After the reaction, the resulting mixture was dried at 60°C for 6 hours to obtain a powdery M-phase vanadium dioxide micro-flower composite graphene oxide material.
[0056] 3. Preparation of VO2(M) microflower-GO positive electrode active material aqueous zinc ion battery
[0057] The prepared M-phase vanadium dioxide micro-flower composite graphene oxide material is used as the positive electrode active material of the positive electrode of an aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, and an appropriate amount of NMP is added. The mixture is stirred and mixed evenly to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of the aqueous zinc ion battery. The diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a diaphragm, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte. The existing button battery assembly technology is used to assemble a button-type aqueous zinc ion battery.
[0058] Figure 2 The XRD pattern of the M-phase vanadium dioxide microflower composite graphene oxide material prepared in this embodiment; Figure 2 It can be seen that the peak value corresponds well to the card PDF#09-0142, indicating that the M-phase vanadium dioxide and graphene oxide are successfully composited, and the prepared material is the desired M-phase vanadium dioxide microflower composite graphene oxide material.
[0059] Figure 3 The SEM images of the M-phase vanadium dioxide microflower composite graphene oxide material prepared in this example, a) is a SEM image with a scale of 1 μm, and b) is a SEM image with a scale of 200 nm; Figure 3 It can be seen that the M-phase vanadium dioxide with 3D micro-flower morphology is uniformly deposited on the graphene oxide. The M-phase vanadium dioxide is closely adjacent to the graphene oxide, and there are abundant heterogeneous interfaces, which provide a large number of crystal defects and active sites. When the composite material is used in aqueous zinc-ion batteries, it can effectively promote ion / electron transfer and improve electronic conductivity, and at the same time effectively prevent the collapse of the structure during the (de)embedding process of zinc ions.
[0060] The aqueous zinc ion battery prepared in this example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are also shown in Table 1.
[0061] The aqueous zinc ion battery prepared in this embodiment was subjected to a high current long cycle test, with the voltage range set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, it was cycled for 1000 cycles at a high current density of 5 A / g. The test results showed that the first cycle discharge capacity was 329.36 mAh / g, and after 1000 cycles, it still maintained a high capacity of 290.88 mAh / g, with a capacity retention rate of 88.32%, indicating that the aqueous zinc ion battery prepared in this embodiment has excellent high current long cycle performance.
[0062] The aqueous zinc ion battery prepared in this embodiment was subjected to a rate test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled for 5 cycles at current densities of 0.1, 0.3, 0.5, 1, 2, 3, 4, 5, and 0.1 A / g, respectively. The test results are shown in FIG. Figure 4 shown.
[0063] Figure 4 The rate performance diagram of the aqueous zinc ion battery using the M-phase vanadium dioxide microflower composite graphene oxide material prepared in this embodiment as the positive electrode active material is shown in FIG. Figure 4 It can be seen that after the aqueous zinc-ion battery was activated for two cycles at 0.05 A / g, it was cycled for 5 cycles at current densities of 0.1, 0.3, 0.5, 1, 2, 3, 4, 5, and 0.1 A / g, and the average specific capacity was 522.62, 506.55, 490.58, 469.61, 439.59, 403.46, 373.42, 324.81, and 485.58 mAh / g, respectively, showing excellent rate performance.
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that: the M-phase vanadium dioxide with 3D micro-flower morphology is mixed with 0.1 mg / mL of ethanol dispersion of monolayer graphene oxide at a rate of 0.007 g / 5 mL (i.e., the mass ratio of M-phase vanadium dioxide: monolayer graphene oxide is 14:1), and the rest of the contents are the same as those described in embodiment 1. The specific preparation process is as follows:
[0066] 1. Preparation of M-phase vanadium dioxide with 3D micro-flower morphology
[0067] As described in Example 1.
[0068] 2. Preparation of M-phase vanadium dioxide microflower composite graphene oxide materials
[0069] The prepared 3D micro-flower morphology of M-phase vanadium dioxide was mixed with 0.1 mg / mL of a single-layer graphene oxide dispersion (the solvent was ethanol, commercially available) at a ratio of 0.007 g / 5 mL (i.e., the mass ratio of M-phase vanadium dioxide: single-layer graphene oxide was 14:1); the resulting mixture was first subjected to ultrasonic reaction for 1 hour at an ultrasonic power of 55 W, and then magnetically stirred at room temperature for 6 hours. After the reaction, the resulting mixture was dried at 60°C for 6 hours to obtain a powdered M-phase vanadium dioxide micro-flower composite graphene oxide material.
[0070] 3. Preparation of VO2(M) microflower-GO positive electrode active material aqueous zinc ion battery
[0071] The prepared M-phase vanadium dioxide micro-flower composite graphene oxide material is used as the positive electrode active material of the positive electrode of an aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, and an appropriate amount of NMP is added. The mixture is stirred and mixed evenly to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of the aqueous zinc ion battery. The diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a diaphragm, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte. The existing button battery assembly technology is used to assemble a button-type aqueous zinc ion battery.
[0072] The aqueous zinc ion battery prepared in this example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are also shown in Table 1.
[0073] Comparative Example 1
[0074] The difference between this embodiment and embodiment 1 is that the positive electrode active material used in the aqueous zinc ion battery is M-phase vanadium dioxide with a 3D micro-flower morphology, and the rest of the contents are the same as those described in embodiment 1. The specific preparation process is as follows:
[0075] 1. Preparation of M-phase vanadium dioxide with 3D micro-flower morphology
[0076] As described in Example 1.
[0077] 2. Preparation of VO2(M) micro-flower positive electrode active material aqueous zinc ion battery
[0078] The prepared M-phase vanadium dioxide with 3D microflower morphology is used as the positive electrode active material of the positive electrode of an aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, and an appropriate amount of NMP is added. The mixture is stirred and mixed evenly to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of an aqueous zinc ion battery. The diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a separator, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte. The existing button battery assembly technology is used to assemble a button-type aqueous zinc ion battery.
[0079] The aqueous zinc ion battery prepared in this comparative example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are also shown in Table 1.
[0080] The aqueous zinc ion battery prepared in this comparative example was subjected to a rate test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled for 5 cycles at current densities of 0.1, 0.3, 0.5, 1, 3, 5, and 0.1 A / g, respectively. The test results are shown in FIG. Figure 4 shown.
[0081] Figure 5 The rate performance diagram of the aqueous zinc ion battery using the 3D micro-flower morphology of M-phase vanadium dioxide as the positive electrode active material prepared in this comparative example is shown in FIG. Figure 4 It can be seen that after the aqueous zinc-ion battery was activated for two cycles at 0.05 A / g, it was cycled for 5 cycles at current densities of 0.1, 0.3, 0.5, 1, 3, 5, and 0.1 A / g, and the average specific capacities were 472.82, 327.89, 302.59, 251.04, 177.71, 161.90, and 271.88 mAh / g, respectively.
[0082] Combined with Example 2 Figure 4 And the comparative example Figure 5 The results show that the aqueous zinc-ion battery using M-phase vanadium dioxide microflower composite graphene oxide material as the positive electrode active material has better rate performance than the aqueous zinc-ion battery using M-phase vanadium dioxide with 3D microflower morphology as the positive electrode active material. This shows that the graphene oxide material in the M-phase vanadium dioxide microflower composite graphene oxide material has a large specific surface area and a flexible structure, which not only improves the electrode reaction kinetics, but also provides buffering and protection for the volume change of vanadium-based positive electrode materials, thereby enhancing the structural stability of vanadium-based positive electrode materials.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 1 is that the positive electrode active material used in the aqueous zinc ion battery is rod-shaped M-phase vanadium dioxide, and the rest of the contents are the same as those described in Example 1. The specific preparation process is as follows:
[0085] 1. Preparation of Rod-Shaped M-Phase Vanadium Dioxide
[0086] a) dissolving 2 g of V2O5 and 6 g of anhydrous oxalic acid in 30 mL of deionized water, and then stirring and reacting at 60° C. for 5 hours to obtain a vanadium oxalate solution, which is blue;
[0087] b) transferring the obtained vanadium oxalate solution into a reactor liner, performing a hydrothermal reaction at 180° C. for 24 hours, centrifuging the reaction solution, and washing the separated precipitate three times by centrifugation with a 30% ethanol aqueous solution as a washing liquid, and then drying at 60° C. for 6 hours to obtain a powdered comparative primary product;
[0088] c) The powdered comparison primary product is transferred into a crucible, and then the crucible containing the product is placed in a muffle furnace. Under the protection of argon, the temperature is first increased to 350°C at a heating rate of 10°C / min, and the product is first calcined at this temperature for 2 hours. After the calcination, the product is cooled to room temperature with the furnace, and then the temperature is increased to 350°C at a heating rate of 10°C / min, and the product is secondarily calcined at this temperature for 2 hours. After the calcination, the product is air-cooled to room temperature to obtain rod-shaped M-phase vanadium dioxide.
[0089] 2. Preparation of VO2(M) rod-shaped positive electrode active material for aqueous zinc-ion batteries
[0090] The prepared rod-shaped M-phase vanadium dioxide is used as a positive electrode active material of an aqueous zinc ion battery positive electrode, the positive electrode active material: acetylene black: polyvinylidene fluoride are mixed according to a mass ratio of 7:2:1, and an appropriate amount of NMP is added, and the mixture is stirred and mixed evenly to form a positive electrode slurry, and then the obtained positive electrode slurry is coated on the surface of a stainless steel mesh, and dried to obtain a positive electrode sheet of the aqueous zinc ion battery, and the diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery, a zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a diaphragm, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte, and an existing button battery assembly technology is adopted to assemble a button-type aqueous zinc ion battery.
[0091] Figure 6 TEM image of the rod-shaped M-phase vanadium dioxide prepared in this comparative example. Figure 6 It can be seen that the morphology of the M-phase vanadium dioxide formed without the addition of hydrogen peroxide and ethanol reducing agent is a rod-like structure. Compared with the M-phase vanadium dioxide with a 3D micro-flower morphology prepared in Example 1, the composite of the rod-like M-phase vanadium dioxide and the layered graphene is not conducive to the exposure of active sites.
[0092] The aqueous zinc ion battery prepared in this comparative example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are also shown in Table 1.
[0093] Comparative Example 3
[0094] The difference between this comparative example and Example 1 is that the positive electrode active material used in the aqueous zinc ion battery is a rod-shaped M-phase vanadium dioxide composite graphene oxide material obtained by combining rod-shaped M-phase vanadium dioxide and graphene oxide. The rest of the contents are the same as those described in Example 1. The specific preparation process is as follows:
[0095] 1. Preparation of Rod-Shaped M-Phase Vanadium Dioxide
[0096] a) dissolving 2 g of V2O5 and 6 g of anhydrous oxalic acid in 30 mL of deionized water, and then stirring and reacting at 60° C. for 5 hours to obtain a vanadium oxalate solution, which is blue;
[0097] b) transferring the obtained vanadium oxalate solution into a reactor liner, performing a hydrothermal reaction at 180° C. for 24 hours, centrifuging the reaction solution, and washing the separated precipitate three times by centrifugation with a 30% ethanol aqueous solution as a washing liquid, and then drying at 60° C. for 6 hours to obtain a powdered comparative primary product;
[0098] c) The powdered comparison primary product is transferred into a crucible, and then the crucible containing the product is placed in a muffle furnace. Under the protection of argon, the temperature is first increased to 350°C at a heating rate of 10°C / min, and the product is first calcined at this temperature for 2 hours. After the calcination, the product is cooled to room temperature with the furnace, and then the temperature is increased to 350°C at a heating rate of 10°C / min, and the product is secondarily calcined at this temperature for 2 hours. After the calcination, the product is air-cooled to room temperature to obtain rod-shaped M-phase vanadium dioxide.
[0099] 2. Preparation of Rod-like M-phase Vanadium Dioxide Composite Graphene Oxide Materials
[0100] The prepared rod-shaped M-phase vanadium dioxide was mixed with 0.1 mg / mL of an ethanol dispersion of single-layer graphene oxide at a ratio of 0.005 g / 5 mL (i.e., the mass ratio of rod-shaped M-phase vanadium dioxide: single-layer graphene oxide was 10:1); the resulting mixture was first subjected to ultrasonic reaction for 1 hour with an ultrasonic power of 55 W, and then magnetically stirred at room temperature for 6 hours. After the reaction, the resulting mixture was dried at 60°C for 6 hours to obtain a powdery rod-shaped M-phase vanadium dioxide composite graphene oxide material.
[0101] 3. Preparation of VO2(M) rod-GO positive electrode active material for aqueous zinc-ion batteries
[0102] The prepared rod-shaped M-phase vanadium dioxide composite graphene oxide material is used as the positive electrode active material of the positive electrode of an aqueous zinc ion battery. The positive electrode active material: acetylene black: polyvinylidene fluoride are mixed according to a mass ratio of 7:2:1, and then an appropriate amount of NMP is added, and the mixture is stirred and mixed evenly to form a positive electrode slurry. The obtained positive electrode slurry is then coated on the surface of a stainless steel mesh and dried to obtain a positive electrode sheet of the aqueous zinc ion battery. The diameter of the positive electrode sheet is cut into 12 mm, and the cut positive electrode sheet is used as the positive electrode of the aqueous zinc ion battery. A zinc foil (with a purity of 99.9% and a thickness of 2 mm) is used as a negative electrode, a glass fiber is used as a diaphragm, and a 3M Zn(CH3F3SO3)2 aqueous solution is used as an electrolyte. The existing button battery assembly technology is used to assemble a button-type aqueous zinc ion battery.
[0103] The aqueous zinc ion battery prepared in this comparative example was subjected to a cyclic voltammetry test. During the test, the voltage range was set to 0.4-1.6 V. After two cycles of activation at 0.05 A / g, the battery was cycled 50 times at a current density of 0.5 A / g. The test results are also shown in Table 1.
[0104] Table 1 Cyclic voltammetry test results of aqueous zinc ion batteries prepared in Examples 1-3 and Comparative Examples 1-3
[0105] Zinc ion battery First cycle discharge capacity (mAh / g) 50-cycle discharge capacity (mAh / g) Capacity retention rate (%) Example 1 458.64 387.93 84.58 Example 2 502.35 431.83 85.96 Example 3 400.69 342.51 85.48 Comparative Example 1 400.04 310.45 77.60 Comparative Example 2 353.01 123.77 35.06 Comparative Example 3 376.87 279.01 74.19
[0106] As can be seen from Table 1, under the same conditions, the aqueous zinc ion battery using M-phase vanadium dioxide microflower composite graphene oxide material as the positive electrode active material (Examples 1-3) has better discharge specific capacity and cycle stability than the aqueous zinc ion battery using rod-shaped M-phase vanadium dioxide composite graphene oxide material as the positive electrode active material (Comparative Example 3), and the aqueous zinc ion battery using 3D microflower morphology of M-phase vanadium dioxide as the positive electrode active material (Comparative Example 1) has better discharge specific capacity and cycle stability than the aqueous zinc ion battery using rod-shaped M-phase vanadium dioxide as the positive electrode active material (Comparative Example 2), indicating that the morphology of M-phase vanadium dioxide has a significant effect on the discharge specific capacity and cycle stability of the final aqueous zinc ion battery;
[0107] In addition, the aqueous zinc ion battery using M-phase vanadium dioxide microflower composite graphene oxide material as the positive electrode active material (Examples 1-3) has better cycle stability than the aqueous zinc ion battery using M-phase vanadium dioxide with 3D microflower morphology as the positive electrode active material (Comparative Example 1), and the aqueous zinc ion battery using rod-shaped M-phase vanadium dioxide composite graphene oxide material as the positive electrode active material (Comparative Example 3) has better cycle stability than the aqueous zinc ion battery using rod-shaped M-phase vanadium dioxide as the positive electrode active material (Comparative Example 2), indicating that graphene oxide has a significant effect on the cycle stability of the final aqueous zinc ion battery;
[0108] In addition, the aqueous zinc ion battery of Example 2 has better specific capacity and cycle stability than the aqueous zinc ion batteries of Example 1 and Example 3, indicating that the mass ratio of M-phase vanadium dioxide to graphene oxide has a certain influence on the performance of the final aqueous zinc ion battery.
[0109] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.
Claims
1. An M-phase vanadium dioxide microflower composite graphene oxide material, characterized in that: It consists of graphene oxide and M-phase vanadium dioxide with a 3D micro-flower morphology supported on graphene oxide.
2. The M-phase vanadium dioxide microflower composite graphene oxide material according to claim 1, characterized in that: The preparation of the M-phase vanadium dioxide with 3D micro-flower morphology comprises the following steps: a) dissolving vanadium pentoxide and anhydrous oxalic acid in water, and then stirring and reacting at 55-75° C. for 5-10 hours to obtain a vanadium oxalate solution; b) cooling the vanadium oxalate solution to room temperature, then adding hydrogen peroxide to the vanadium oxalate solution, stirring at room temperature for 25 to 50 minutes, then adding ethanol to the obtained reaction system, and then hydrothermally reacting at 170 to 200° C. for 20 to 24 hours. After the reaction is completed, collecting the solid product to obtain a powdery primary product; c) The powdered primary product is placed in a muffle furnace, and under protective gas conditions, it is first calcined at 350-550° C. for 2-3 hours. After the calcination, it is cooled to room temperature with the furnace, and then calcined at 350-550° C. for 2-3 hours. After the calcination, it is air-cooled to room temperature to obtain M-phase vanadium dioxide with a 3D micro-flower morphology.
3. The M-phase vanadium dioxide microflower composite graphene oxide material according to claim 2, characterized in that: During the preparation process, the feed ratio of vanadium pentoxide, anhydrous oxalic acid, hydrogen peroxide and ethanol is (0.2-0.6) g: (0.6-1.2) g: (5-8) mL: (50-100) mL.
4. A method for preparing the M-phase vanadium dioxide microflower composite graphene oxide material according to claim 1, characterized in that: The following operations are included: The M-phase vanadium dioxide with 3D micro-flower morphology and the ethanol dispersion of graphene oxide are mixed at room temperature; the obtained mixed solution is first subjected to ultrasonic reaction for 1 to 1.5 hours, and then stirred at room temperature for 5 to 6 hours. After the reaction, the obtained mixed solution is dried at 55 to 65° C. for 6 to 12 hours to obtain the M-phase vanadium dioxide micro-flower composite graphene oxide material.
5. The method for preparing the M-phase vanadium dioxide microflower composite graphene oxide material according to claim 4, characterized in that: The concentration of the ethanol dispersion of graphene oxide is 0.1 to 0.5 mg / mL, the amount of M-phase vanadium dioxide added is 5 to 15 mg, and the amount of the ethanol dispersion of graphene oxide added is 1 to 10 mL.
6. An application of the M-phase vanadium dioxide microflower composite graphene oxide material according to claim 1 in the positive electrode of an aqueous zinc ion battery, characterized in that: Used as positive electrode active material for aqueous zinc ion battery positive electrode.
7. A method for preparing a positive electrode for an aqueous zinc ion battery, characterized in that: The following operations are included: The M-phase vanadium dioxide microflower composite graphene oxide material according to claim 1 is used as a positive electrode active material, the positive electrode active material, the conductive agent, the binder and the solvent are evenly mixed to form a positive electrode slurry, and the obtained positive electrode slurry is coated on the surface of the positive electrode collector and dried at 55 to 65° C. for 6 to 12 hours to obtain an aqueous zinc ion battery positive electrode.
8. The method for preparing an aqueous zinc ion battery positive electrode according to claim 7, wherein: The conductive agent is acetylene black, the binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, and the mass ratio of the positive electrode active material: the conductive agent: the binder is 7:2:
1.
9. An aqueous zinc ion battery, characterized in that: The invention comprises a positive electrode and a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an aqueous electrolyte, wherein the positive electrode is the positive electrode of the aqueous zinc ion battery prepared according to claim 7, the negative electrode is zinc foil, the separator is glass fiber, and the aqueous electrolyte is a 3M Zn(CH3F3SO3)2 aqueous solution.
Citation Information
Patent Citations
Vanadium pentoxide / graphene composite material and preparation method and application thereof
CN109980205A
A carbon nanotube / M-phase vanadium dioxide composite structure, its preparation method, and its application in aqueous zinc-ion batteries.
CN110838583B